Relevance of trypanothione reductase inhibitors on trypanosoma cruzi infection - Mendonça, Andrea Aparecida Dos Santos (2020)
Due to the rudimentary antioxidant defenses in trypanosomatids, disruptors of redox balance, especially trypanothione reductase (TR) inhibitors, are promising candidates for new antitrypanosomal drugs. However, the relevance of these drugs in the treatment of Chagas disease remains poorly explored. From primary and secondary investigations, we analyzed the relevance of TR inhibitors in the treatment of T. cruzi infection in vivo. In our secondary approach, we used an integrated framework based on systematic review, meta-analyses and molecular modeling. Our findings indicated that the TR inhibitors analyzed, especially clomipramine and thioridazine, presented no beneficial effects on infection-related electrocardiographic abnormalities. However, were effective in reducing parasitemia and mortality in T. cruzi-infected mice. The affinity between TR inhibitors and TR was confirmed by molecular docking. However, the molecular affinity score was unable to explain TR inhibition and the anti-parasitic potential of these drugs in vitro and in vivo, indicating that the anti-T. cruzi effects may not be restricted to TR inhibition. As in vivo studies on TR inhibitors are scarce and exhibit methodological limitations, mechanistic and highly controlled studies are required to improve the quality of evidence. From this observations, we used a murine model of Chagas disease to compare the antiparasitic potential of thioridazine (TDZ) and benznidazole (Bz) administered in monotherapy and combined. Female Swiss mice were randomized into six groups: (i) uninfected untreated, (ii) infected untreated and infected and treated with (iii) Bz (100 mg/kg), (iv) TDZ (80 mg/kg), (v) Bz (100 mg/kg) + TDZ (80 mg/kg), (vi) Bz (50 mg/kg) + TDZ (80 mg/kg). Infected animals were inoculated with 2000 T. cruzi trypomastigotes (Y strain) and treated by gavage during 20 days. The animals treated with TDZ presented the highest levels of parasitemia, parasitic load, anti-T. cruzi immunoglobulin G plasma titers, plasma and/or cardiac cytokine levels (IFN-γ, TNF-α, IL-10 and IL-17), as well as cardiac, skeletal muscle and hepatic damage compared to the other groups (P<0.05). These parameters were significantly reduced in the group treated with Bzbased monotherapy compared to the other infected groups (P<0.05). The combination of TDZ with Bz at the therapeutic dose (100mg/kg) and mainly at half of this dose attenuated the response to treatment, worsening parasitological control, systemic and tissue inflammation, as well as microstructural lesions of all organs investigated compared to the group treated with Bz alone (P<0.05). Thus, our results indicated that when administered alone, TDZ potentiated pathological outcomes in T. cruzi-infected animals. Because TDZ attenuated the antiparasitic effect of Bz, impairing parasitological control and potentiating inflammation and pathological remodeling of the heart, skeletal muscle and liver; Bz-based monotherapy remains a better option for the treatment of experimental Chagas disease.